2012
DOI: 10.1002/adfm.201200536
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitecture Multi‐Structural Cathode Materials for High Capacity Lithium Batteries

Abstract: Lithium‐rich composite cathodes have been extensively investigated for lithium‐ion batteries. Nanoarchitecture hydroxide precursor for these cathodes with two levels of particle agglomeration (1–2 μm and 10 μm) is produced using a co‐precipitation method. Transmission electron microscopy and X‐ray diffraction confirm that the precursor is a composite comprising transition metal hydroxides and Mn3O4. Cathode materials synthesized based on the precursor are “layered (R$ \bar 3 $m)‐layered (C2/m)‐spinel (Fd$ \bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
119
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(129 citation statements)
references
References 33 publications
10
119
0
Order By: Relevance
“…6 correspond to a Mn 3 O 4 phase (space group I4 1 /amd), which is the result of Mn 2þ oxidation. Select area electron diffraction confirmed the precursor was TM(OH) 2 rather than TMOOH, which was discussed in detail in our previous study [32]. The composite structure of the precursors indicates that even though N 2 cover gas was applied during the synthesis process, a certain amount of Mn 2þ oxidized to Mn 3þ during synthesis, washing, or drying.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…6 correspond to a Mn 3 O 4 phase (space group I4 1 /amd), which is the result of Mn 2þ oxidation. Select area electron diffraction confirmed the precursor was TM(OH) 2 rather than TMOOH, which was discussed in detail in our previous study [32]. The composite structure of the precursors indicates that even though N 2 cover gas was applied during the synthesis process, a certain amount of Mn 2þ oxidized to Mn 3þ during synthesis, washing, or drying.…”
Section: Resultssupporting
confidence: 55%
“…The peak intensity at glomerates are narrowly distributed. A process involving two levels of particle agglomeration (1e2 mm and 10 mm) was proposed in our previous report [32]. We concluded that even though the growth rates varied for experiments with different M S /M A ratios, the particle growth follows the same two-level agglomeration mechanism.…”
Section: Resultsmentioning
confidence: 51%
“…In contrast, it is found that these two pairs of well-separated peaks are combined into broad (222) S and (440) S peaks at 500 °C in portions III and IV, respectively, revealing a complete layered-to-spinel phase transformation. [ 14 ] Increasing the annealing temperature above 600 °C causes undesired decomposition of the newly formed spinel structure, resulting in a MnCo 2 O 4 impurity and recovery of layered Li 2 MnO 3 , which is consistent with the continuous mass reduction in the TG curves during the heating segment. Formation of MnCo 2 O 4 is apparently detected at 600 °C in portion II at 2 θ = 30° -31°, and the restored layered Li 2 MnO 3 is confi rmed by the obvious intensity increase of its XRD peaks in portions I, III, and IV.…”
Section: Introductionsupporting
confidence: 67%
“…[ Protonation is the prerequisite for the second ion-exchange process, which also results in a distinct morphological change in the LHMNCO derivative and induces formation of a detectable spinel phase within a predominant layered structure. The scanning electron microscopy (SEM) image in Figure 2 b shows distinct layered cake-shaped LHMNCO blocks, which are drastically different from solid polyhedrons of the original LMNCO (Figure 2 a) 14 ] As such, the merger of well-separated (113) M /(006) R and (131) M /(012) R doublets indicates a certain degree of distortion in the layered structure, while the peak splits of (108) R -(110) R pair are preserved, showing that the layered structure is mainly retained in the protonated intermediate. [ 14 ] Since the vibrational models involving the Mn−O bonds in the layered structure are different from those in the spinel phase, Raman spectroscopy is also used to confi rm the formation of spinel structures.…”
Section: Introductionmentioning
confidence: 99%
“…Improved battery performance is closely related to the development of materials for various battery components. Except for numerous achievements on high-density positive materials [4][5][6][7][8], the enhancement in energy density is also closed related to the application of novel electrolytes with high potential windows and stability. Lithium hexafluorophosphate (LiPF 6 ) is commonly used as electrolyte salt in commercial LIBs.…”
Section: Introductionmentioning
confidence: 99%